Decision feedback equalization in the context of enhanced high rate mobile communications systems - based on the concept of SC/FDE - Witschnig, Harald; Weigel, Robert (15th IEEE International Symposium on Personal, Indoor and Mobile Radio Communications, 2004)
Although nonlinear equalizer structures seem to be a well developed theory, these equalizer structures are rarely investigated in an overall system approach. It is the topic of this paper to point out that it is inevitable to characterize decision feedback equalizer structures (DFE) in the context of channel characteristics, error propagation and implementation effort before talking of performance gain compared to linear equalizer structures. In particular DFE is characterized in the context of antenna diversity and channel coding as these techniques are indispensable for future high rate wireless communications systems. Only this overall system approach allows a reliable statement concerning the expected performance gain due to different equalizer strategies. The simulation results in this work are based on a single carrier system with frequency domain equalization (SC/FDE), as this concept allows an advantageous combination of feedforward frequency domain equalization and feedback equalization in the time domain, combining low signal processing complexity and powerful equalization. The simulation parameters are adapted to the parameters of the IEEE 802.11a standard.
elib2cris::1512001600,witschnig2004b
Keywords: IEEE standards; channel coding; decision feedback equalisers; diversity reception; feedforward; mobile radio; wireless LAN; DFE; IEEE 802.11a standard; SC/FDE; antenna diversity; channel coding; decision feedback equalization; enhanced high rate mobile communications systems; feedforward frequency domain equalization; mobile radio communications; time domain feedback; Antennas and propagation; Channel coding; Context; Decision feedback equalizers; Diversity reception; Frequency domain analysis; Mobile communication; Performance gain; Signal processing; Wireless communication